2020
DOI: 10.1590/fst.32919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil type and batter ingredients on the properties of deep-frying flakes

Abstract: Deep-fried batter food products have recently gained popularity since they are both appetizing and palatable. However, deep-fried food contains high oil content, promoting increasing health concerns of consumers. Oil absorption reduction batter formulae and new types of cooking oil are showing improved customer demand. Coconut oil is gaining interest as a healthy food selection but information comparing coconut oil to palm oil for frying is limited. Effects of oil type and ingredients on the properties of deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Regarding oil uptake (%) as seen in Table 4, similar observation was noticed as like moisture loss (%). The result is supported by Arshad et al (2019), Lim et al (2012, Surojanametakul et al (2020), and Kim et al (2014).…”
Section: Moisture Loss and Oil Uptake Of Dough In Fryingmentioning
confidence: 68%
“…Regarding oil uptake (%) as seen in Table 4, similar observation was noticed as like moisture loss (%). The result is supported by Arshad et al (2019), Lim et al (2012, Surojanametakul et al (2020), and Kim et al (2014).…”
Section: Moisture Loss and Oil Uptake Of Dough In Fryingmentioning
confidence: 68%
“…The increase in sensory perceptions at low levels of NSF was possibly associated with an increase in crust brittleness because soy flour is rich in both protein and fiber as compared to rice flour. The addition of protein and fiber in starch‐based fried products reduces the hardness and stiffness of the products and makes them more crispy due to the disruption of the starch matrix (Dueik et al., 2014 ; Surojanametakul et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the free radical scavenging activity of curcumin can be due to the presence of high amounts of natural antioxidants with higher reductive capacity. Surojanametakul et al (2010) found that when the concentration of turmeric increases, the free radicals absorption by DPPH were decreased, and it is elevating sensitivity to radical scavenging. In general, the ethanol extract had contained high amounts of antioxidant characteristics than those in the aqueous extract (Tanvir et al, 2017).…”
Section: Antioxidant Activity Of Curcumin Extracts At Different Concentrationsmentioning
confidence: 98%